Microsoft Teams dan Efektivitas Kerja Pegawai KPP Pratama Langsa dalam Meningkatkan Kolaborasi Tim, Komunikasi, dan Kinerja Organisasi - Putris Elianka; Rahmi Meutia; Dhian Rosalina (Manajemen Kreatif Jurnal, 2025)
The rapid advancement of digital collaboration platforms has reshaped the way organizations manage communication, motivation, and performance. Microsoft Teams, as one of the most widely adopted tools, provides integrated features for real-time messaging, virtual meetings, and document sharing that enable employees to collaborate more effectively. This study aims to explore the impact of Microsoft Teams on communication, motivation, and employee performance at the Pratama Tax Service Office (KPP) in Langsa. A quantitative research design was applied using a survey method, with data collected through pretest and posttest questionnaires. The study involved a total population of 89 employees, of which 81 valid responses were analyzed. Data processing was carried out with SPSS version 25 to compare employee conditions before and after the use of Microsoft Teams. The findings reveal that the adoption of Microsoft Teams contributes to more effective communication, enhances employee motivation by simplifying coordination and task management, and improves overall performance. These results highlight the potential of digital collaboration platforms to strengthen organizational effectiveness, particularly in government institutions that require efficiency, transparency, and adaptability in their operations. The study further implies that maximizing the use of digital platforms can support long-term organizational goals in the context of ongoing digital transformation.